Disabilities in Roman antiquity : disparate bodies, a capite ad calcem - Laes, Christian.; Goodey, C. F.; Rose, Martha L., 1957- (Mnemosyne, Supplements, 2013)
This is the first volume ever to systematically study the subject of disabilities in the Roman world. The contributors examine the topic a capite ad calcem , from head to toe. Chapters deal with mental and intellectual disability, alcoholism, visual impairment, speech disorders, hermaphroditism, monstrous births, mobility problems, osteology and visual representations of disparate bodies. The authors fully engage with literary, papyrological, and epigraphical sources, while iconography and osteo-archaeology are taken into account. Also the late ancient evidence is taken into account. Refraining from a radical constructionist standpoint, the contributors acknowledge the possibility of discovering significant differences in the way impairment was culturally viewed or assessed.